Chondrocyte Adipogenic Differentiation in Softening Osteoarthritic Cartilage. (June 2022) - Xu, X.; Chu, Y.; Zhang, Y.; Li, G.; Yang, P.; Zhang, J.; Duan, J.; Yang, H.; Xu, H.; Wang, M.
A chondrocyte-to-osteoblast lineage continuum exists in the growth plate. Adipogenic differentiation of chondrocytes in vivo should be investigated. Here, unilateral anterior crossbite (UAC), which can induce osteoarthritic lesions in the temporomandibular joint (TMJ), was applied to 6-wk-old C57BL/6 mice. Matrix loss in TMJ cartilage was obvious, as demonstrated by safranin O staining, and the condylar cartilage elastic modulus values, detected by using atomic force microscopy (AFM), were reduced, indicating cartilage softening that might be linked with loss of the highly charged proteoglycan. By crossing the Rosa26/tdTomato (TdT) mice with Sox9;Cre ERT2 mice or with Col10;Cre ERT2 mice, we obtained the Sox9-TdT and Col10-TdT strains, respectively, in which the Sox9- or Col10-expressing cells, accordingly, were labeled by TdT. A few TdT-labeled cells in both strains expressed AdipoQ or DMP-1. The Sox9-TdT + AdipoQ + cells were primarily located in the deep zone cartilage and then in the whole cartilage. Col10-TdT + AdipoQ + cells, Sox9-TdT + DMP-1 + cells, and Col10-TdT + DMP-1 + cells were located in the deep zone region. UAC promoted AdipoQ and DMP-1 expression in cartilage. The percentages of Sox9-TdT + AdipoQ + and Col10-TdT + AdipoQ + cells to Sox9-TdT + and Col10-TdT + cells, respectively, were increased (both P < 0.05), implying that more chondrocytes were undergoing adipogenic differentiation in the UAC group, the cartilage of which was softened. The percentages of Sox9-TdT + DMP-1 + and Col10-TdT + DMP-1 + cells to Sox9-TdT + cells and Col10-TdT + cells, respectively, were increased (both P < 0.05), consistent with our report that UAC enhanced deep zone cartilage calcification, causing stiffening of the deep zone cartilage. Our present data demonstrated that TMJ chondrocyte descendants can become adipogenic in vivo in addition to becoming osteogenic. This potential was promoted in osteoarthritic cartilage, in which deep zone cartilage calcification-associated cartilage stiffening and proteoglycan loss-associated cartilage softening were both stimulated.